Structural alterations during mechanochemical activation of a titanium-magnetite mixture - Cristobal, Adrian Alberto (2008)
In this work, mechanochemical activation and thermal behaviour of (Ti + Fe3O4) mixtures in Ti/Fe3O4 molar ratios 0.5, 1, and 1.5, are studied. The samples were activated under Ar atmosphere, thermally treated at temperatures ranging between 400 and 700 °C, and analyzed by XRD and Rietveld analysis, SEM and EPMA. By XRD, a progressive decrease in crystallinity with the activation time of was observed. For the samples with lower Ti contents, the system evolved towards the formation of a ulvospinel (Fe2TiO4)-magnetite (Fe3O4) solid solution, while for higher Ti contents the major phase obtained was ilmenite (FeTiO3). During the activation at room temperature, low crystalline intermediate phases (FeO + TiO, FeO, pseudobrookite [Fe2TiO5]) were generated, depending on the initial mixture composition. Thermal treatments resulted in a progressive structural ordering, with lattice parameters slightly greater than those of the original spinel. These results suggest that during the activation at room temperature, the Ti reduces the Fe of the spinel and partially replaces it in the lattice.